Prognostic and Clinicopathological Significance of Long Non-coding RNA PANDAR Expression in Cancer Patients: A Meta-Analysis - Han, Lizhi; Wang, Bo; Wang, Ruoyu; Wang, Zijian; Gong, Song; Chen, Guo; Telemacque, Dionne; Feng, Yong; Xu, Weihua (Frontiers in Oncology, 2019)
Background: Long non-coding RNA PANDAR is an emerging non-coding RNA mapping to 6p21.2. It underlies metastatic progression and chromosomal instability in a variety of cancers. Despite the fact that recent studies have revealed that lncRNA PANDAR may be a potential prognostic biomarker for patients with cancer, there has still been controversy on the prognostic value of PANDAR. Methods: Databases of PubMed, Embase, SinoMed, and Web of Science were carefully searched and the literature which investigated the prognostic value of PANDAR expression among human cancers was collected for further analysis. Odds ratios (ORs) or hazards ratios (HRs) with 95% confidence intervals (CIs) were pooled to estimate the relation between PANDAR expression and survival or clinicopathological characteristics of cancer patients. Results: There were 13 eligible studies in total, with 1465 patients enlisted in this meta-analysis. The outcome showed that the elevated expression level of PANDAR was significantly related to poor overall survival (OS) (pooled HR 1.72, 95%CI 1.14-2.60). However, high or low expression of PANDAR did not differ in the prediction of event-free survival (EFS). Moreover, we discovered that high PANDAR expression was closely related to decreased OS in colorectal cancer (pooled HR 3.43, 95%CI 2.06-5.72) and reduced expression level of PANDAR was markedly related to poor OS (pooled HR 0.65, 95%CI 0.45-0.88) in non-small cell lung cancer. However, the expression level of PANDAR had no significant association with OS in renal cell carcinoma (pooled HR 1.19, 95%CI 0.56-2.50). Moreover, after analysis, we discovered that the high expression level of PANDAR was associated closely with the depth of invasion (pooled OR 3.95, 95%CI 2.36-6.63), lymph node metastasis (pooled OR 1.92, 95%CI 0.93-3.98), tumor stage (pooled OR 2.05, 95%CI 0.99-4.27) and distant metastasis (pooled OR 2.87, 95%CI 1.60-5.16). Conclusions: Our study revealed that increased PANDAR expression may serve as an adverse prognostic biomarker for cancer patients, thus helping the clinical decision-making process.